Pemberdayaan Masyarakat melalui Edukasi Keagamaan, Literasi Digital, dan Tata Kelola Desa: Studi KKN di Desa Alue Teungoh, Aceh Jaya - Muhammad Ikhwan Adabi; Muhammad Nur; Farhan Rahmatul Maulid; Yusra Arfinda; Sinta Arsandi; M. Andrian Syahputra; Riska Filia; Teuku Khairun Ramadhan; Mulya Fatimah Zuhra (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2026)
This study aims to analyze the role of the Community Service Program (Kuliah Kerja Nyata/KKN) in empowering local communities through religious education, strengthening digital literacy, and enhancing village governance capacity in Alue Teungoh Village, Aceh Jaya Regency. The study is grounded in the need to address socio-religious challenges, digital transformation, and the growing demand for transparency and accountability in village administration in the contemporary era. A qualitative descriptive approach was employed, utilizing field observations, in-depth interviews with village officials and community members, and documentation of KKN activities as data collection techniques. The findings reveal that religious education initiatives contributed to increasing community participation in religious activities and fostering moral development among youth. Digital literacy programs enabled community members, particularly young people and village administrators, to utilize information technology for administrative purposes, promotion of local village potential, and access to public information. Interventions in village governance enhanced officials’ understanding of transparency, accountability, and regulation-based public service principles. The integration of these three dimensions generated a synergistic impact on strengthening the social and institutional capacities of the village community. This study concludes that an empowerment model integrating religious education, digital literacy, and village governance strengthening through KKN is effective in promoting participatory and sustainable social transformation at the village level. These findings offer a conceptual contribution to the development of locally responsive KKN models and community-based rural development strategies.